In vitro antidiabetic activity of facheiro (Pilosocereus pachycladus) mucilage and its effects on glycaemic, renal and hepatic parameters in obese rats - Fabrícia de Souza Ferreira; Hassler Clementino Cavalcante; Larissa Maria Gomes Dutra; Adriano Francisco Alves; Stephson Andriola Almeida Gonçalves; Tatiana Colombo Pimentel; Carlos Eduardo Barão; Marcos dos Santos Lima; Alana Natalícia Vasconcelos de Araújo; Januse Millia Dantas de Araújo; Kamila Sabino Batista; Jailane de Souza Aquino; et al. (Journal of Functional Foods)
We evaluated the in vitro antidiabetic activity of facheiro (Pilosocereus pachycladus) mucilage and its effects on glycaemic, renal and hepatic parameters in obese rats. First, in vitro antidiabetic activity was analysed through the inhibition of α-amylase and α-glucosidase. Then, the acute toxicity of mucilage was evaluated in Wistar rats for 14 days. After, an experiment to evaluate the effects of mucilage on obesity was conducted with 30 male Wistar rats randomised into three groups: healthy (HG); obese (OG); and obese treated with facheiro mucilage (FOG) by gavage (200 mg/kg). The HG received commercial diet and the OG and FOG received a cafeteria diet for 12 weeks. Facheiro mucilage showed antidiabetic activity in vitro by reducing the α-amylase (64.15 ± 3.86 %) and α-glucosidase activity (86.43 ± 1.09 %), without signs of acute toxicity in vivo. Mucilage treatment reduced insulinemia (OG = 29.70 ± 4.52 µIU/mL vs. FOG = 14.04 ± 5.08 µIU/mL, p = 0.01, effect size: 3.25), homeostasis assessment model (OG = 0.99 ± 0.12, FOG = 0.76 ± 0.18, p = 0.03, effect size: 1.50), uric acid (OG = 6.65 ± 1.63 mg/dL vs. FOG = 4.07 ± 0.65 mg/dL, p = 0.0001, effect size: 2.07), creatinine (OG = 0.90 ± 0.08 mg/dL vs. FOG = 1.05 ± 0.15 mg/dL, p = 0.0001, effect size: 1.24), alanine transaminase (OG = 29.70 ± 4.52 IU/L vs. FOG = 14.05 ± 5.08 IU/L, p = 0.0001, effect size: 3.25), aspartate transaminase (OG = 58.55 ± 7.10 IU/L vs. FOG = 22.35 ± 3.61 IU/L, p = 0.0001, effect size: 6.42) and the hepatic steatosis in the FOG compared to the OG. Mucilage intake increased the total concentrations of organic acids and sugars in renal and hepatic tissues of the FOG when compared to the OG. However, overall, it did not alter the murinometric parameters. Our results suggest that facheiro mucilage had antidiabetic activity in vitro, which corroborated the improvement of insulinemia and insulin resistance in FOG rats; in addition, it showed renoprotective and hepatoprotective effects, highlighting a reversal in the severity of hepatic steatosis in obese rats.